1978
DOI: 10.1080/15287397809529654
|View full text |Cite
|
Sign up to set email alerts
|

Variation of properties of chrysotile asbestos subjected to milling

Abstract: Mechanical milling is commonly used to produce short chrysotile asbestos for experimental purposes. Such manipulation also decreases fiber crystallinity, alters Si-O and Mg-O interlayer bonding, induces coordination changes in the brucite layer, diminishes the ability of fiber to reduce specific free radicals and physisorb organic molecules, and decreases hemolytic potency and antagonist sorption capabilities. The degree of alteration is related to the time of milling. Results of biological experimentation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…The more highly opened material had fibers with smaller diameters and greater surface areas. Langer et al (1978) observed that vigorous dry ballmilling of chrysotile reduced its crystallinity as determined by X-ray powder diffraction and changed its surface chemistry as evidenced by IR spectroscopy and diphenylpicrylhydrazyl reduction. Hemolytic potency was reported to have markedly decreased with milling time.…”
Section: Introductionmentioning
confidence: 99%
“…The more highly opened material had fibers with smaller diameters and greater surface areas. Langer et al (1978) observed that vigorous dry ballmilling of chrysotile reduced its crystallinity as determined by X-ray powder diffraction and changed its surface chemistry as evidenced by IR spectroscopy and diphenylpicrylhydrazyl reduction. Hemolytic potency was reported to have markedly decreased with milling time.…”
Section: Introductionmentioning
confidence: 99%
“…5 pm, would otherwise pose few optical problems, but their length makes them most difficult to incorporate in a transparent KBr disk. Extensive grinding would defiberize the material and eventually shorten the length of the fiber bundles, defeating the purpose of this study (24). The 1R spectra of all five materials are very similar and a detailed examination is necessary to identify their distinguishing features.…”
Section: Ir Spectra -Transmission Versus Reflectancementioning
confidence: 99%
“…The appearance of pleural mesotheliomas (following direct implantation in the pleural cavity) correlated best with increasing numbers of fibers having both diameters of 025 ,m or less and lengths of more than 8 tim, but relatively high correlations were also noted with fibers having diameters of up to 1.5 Mm and lengths greater than 4 (6), removal of which by etching enhances the pathogenic effects of the dusts toward animals (7) and macrophages (8). (9) showed that the zeta potential of UICC chrysotile A and crocidolite changed on leaching with HCl or Tyrode's solution and there was a significant correlation between zeta potential and the haemolytic activity of chrysotile and crocidolite.…”
mentioning
confidence: 98%